The effect of liquidity, leverage, and profitability on tax avoidance: Study of food & beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2018-2023 - Fuadi, Ahmad; Tarmidi, Deden (WIM Solusi Prima, 2024)
This study was conducted with the aim of testing and analyzing the effect of liquidity, leverage, and profitability on tax avoidance. This research is a type of quantitative research with the type of data used, namely secondary data obtained from the Company's annual financial statements through the official website of the Indonesia Stock Exchange (IDX). The population of this study is a food and beverage sector company listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. Sampling was carried out using purposive sampling technique so that a sample of 13 companies was obtained that fit the criteria. The data analysis method in this study is multiple linear regression analysis with the data processing software used, namely the Statiscal Package for Social Sciences 26 (SPSS 26) program. The results of this study indicate that Liquidity, Leverage, and Profitability have a significant negative effect on Tax Avoidance.